Distribution of SCCmec-associated phenol-soluble modulin in staphylococci - Monecke, S.; Engelmann, I.; Archambault, M.; Coleman, D.; Coombs, Geoffrey; Cortez de Jäckel, S.; Pelletier-Jacques, G.; Schwarz, S.; Shore, A.; Slickers, P.; Ehricht, R. (2012)
The recently described phenol-soluble modulin PSM-mec was detected in Staphylococcus aureus, Staphylococcus epidermidis, Staphylococcus fleuretti, Staphylococcus hominis, Staphylococcus pseudintermedius, Staphylococcus saprophyticus, Staphylococcus simulans and Staphylococcus vitulinus from different hosts (humans, goats, dogs, cats, pigs, cattle and turkeys). It was identified in isolates harbouring SCC. mec types II, IIA, IIB, IID, III, VIII and in some irregular or truncated elements.